2009
DOI: 10.1097/olq.0b013e3181b01948
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium as a Contributor to the Multiple Etiologies of Cervicitis in Women Attending Sexually Transmitted Disease Clinics

Abstract: Objectives The purpose of this study was to investigate the prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and Mycoplasma genitalium, in women attending a sexually transmitted disease (STD) clinic, as well as the frequency of coinfections, and relationship of each organism to cervicitis. Methods In this cross-sectional study of 324 women attending Baltimore City STD Clinics, C. trachomatis, N. gonorrhoeae, T. vaginalis, and M. genitalium were detected using nucleic acid am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
90
7
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 44 publications
19
90
7
4
Order By: Relevance
“…In the realm of laboratory diagnosis, initial studies of target capture-based transcription-mediated amplification (TMA) in females reported 87.8% (14) We recently demonstrated the utility of TMA-based M. genitalium detection in male specimens originating from both STI and community outpatient clinics (16). In contrast, previous studies of M. genitalium TMA in females have largely focused on high-risk demographics (14,15,(17)(18)(19). Assessment of M. genitalium detection rates in a communitywide setting would be beneficial.…”
mentioning
confidence: 75%
“…In the realm of laboratory diagnosis, initial studies of target capture-based transcription-mediated amplification (TMA) in females reported 87.8% (14) We recently demonstrated the utility of TMA-based M. genitalium detection in male specimens originating from both STI and community outpatient clinics (16). In contrast, previous studies of M. genitalium TMA in females have largely focused on high-risk demographics (14,15,(17)(18)(19). Assessment of M. genitalium detection rates in a communitywide setting would be beneficial.…”
mentioning
confidence: 75%
“…are organisms variably present in rest of cases and often called nonspecific cervicitis (NSC) [2,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In men, M. genitalium is a significant cause of both acute and chronic nongonococcal urethritis (NGU) (5)(6)(7) and is estimated to account for 15% to 25% of cases of NGU in some populations (2). In women, M. genitalium has been significantly associated with both cervicitis (2,(8)(9)(10) and pelvic inflammatory disease (2,(11)(12)(13)(14), and it has been identified in up to 7.3% of women in high-risk populations (15). In Australia, M. genitalium has been reported to account for between 4.5% and 9% of cases of NGU (16,17), while it was identified in 4% of women attending a Sydney sexual health clinic and was the second most common cause of cervicitis (9).…”
mentioning
confidence: 99%